Behavioral Differentiation and Ovarian Development of Unmated Gynes, Queens, and Workers of Ectatomma vizottoi Almeida 1987 (Formicidae, Ectatomminae) - Alexsandro Santana Vieira; Wedson Desidério Fernandes; William Fernando Antonialli-Junior (Psyche: A Journal of Entomology)
Behavioral differentiation and ovarian development of unmated gynes, queens, and workers of Ectatomma vizottoi were investigated in laboratory conditions. Forty-one behavioral acts were identified and quantified for workers, 19 for queens and 24 for unmated gynes, for an overall species repertoire of 42 different behavioral acts. Ovipositing reproductive eggs was an exclusive task of the queen, whereas workers showed 15 caste-specific behaviors. The most important (frequent) behaviors for the queens were brood care, immobility, and reproduction, and for workers were immobility, grooming/interaction, brood care, and foraging. Unmated gynes (not winged) primarily showed immobility, brood care, grooming/interaction, and foraging. Analysis of ovarian development showed that unmated gynes had little-developed ovarioles, in contrast to queens. Queens and unmated gynes showed a clear behavioral differentiation, in which queens played the role of reproducers and unmated gynes performed activities belonging to the worker repertoire. Despite the presence of several breeding queens in the colony, functional monogyny was the rule.